An analysis on geogrid technique in road construction / Muhamad Khairi Johari, Faridah Muhamad Halil - Johari, Muhamad Khairi; Muhamad Halil, Faridah (2018)
In a developing country, there are a lot of road constructions involved especially in rural areas and are still applying conventional techniques in the pavement. Poor roadway geometry can lead to soil settlement caused by heavy load vehicles. Currently, there are many innovations introduced to the construction industry, one of them is geogrid. Geogrids have been used in pavement design for the past 25 years. Geogrid reinforcement is used in permanent paved roadways in two major application areas - base reinforcement and subgrade stabilization. The geogrids are used to build a construction platform over weak subgrades to carry equipment and facilitate the construction of the pavement system without excessive deformations of the subgrade. The aim of the study is to investigate geogrid functions in road stabilization applications and cost-benefit of using geogrids in road construction. The research methodology used in this research is a qualitative method which consists of a case study approach. In conclusion, by using a geogrid technique for road construction, it is cost saving as it is able to reduce the maintenance cost.